1998
DOI: 10.2172/595611
|View full text |Cite
|
Sign up to set email alerts
|

Development of high, stable-efficiency triple-junction a-Si alloy solar cells. Final technical report

Abstract: This publication was reproduced from the best availabk camera-ready copy submiired by the subcontractor and received no editorial review at NREL. NOTICE This report was prepared as an account of work sponsored by an agency of the United States government. Neither the United States government nor any agency thereof, nor any of their emplcyees. makes any warranty, express or implied, or assumes any legal liability or responsibility for the accurzcy, completeness. or usefulness of any information, apparatus, prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…When a-Si is deposited at a lower temperature with higher H dilution, more H is incorporated and the material has a wider band gap. By following the edge of the transition curve (but staying on the amorphous side) while reducing the deposition temperature, wide-gap a-Si and single-junction a-Si n-i-p cells with 1.053 V open-circuit voltage were deposited [76,118]. It was also observed that materials deposited near the edge of microcrystalline formation show intermediate-range structural order [119].…”
Section: Hydrogen Dilutionmentioning
confidence: 99%
“…When a-Si is deposited at a lower temperature with higher H dilution, more H is incorporated and the material has a wider band gap. By following the edge of the transition curve (but staying on the amorphous side) while reducing the deposition temperature, wide-gap a-Si and single-junction a-Si n-i-p cells with 1.053 V open-circuit voltage were deposited [76,118]. It was also observed that materials deposited near the edge of microcrystalline formation show intermediate-range structural order [119].…”
Section: Hydrogen Dilutionmentioning
confidence: 99%
“…When a-Si is deposited at a lower temperature with higher H dilution, more H is incorporated and the material has a wider band gap. By following the edge of the transition curve (but staying on the amorphous side) while reducing the deposition temperature, wide-gap a-Si and single-junction a-Si n-i-p cells with 1.053 V open-circuit voltage were deposited [76,118]. It was also observed that materials deposited near the edge of microcrystalline formation show intermediate-range structural order [119].…”
Section: Hydrogen Dilutionmentioning
confidence: 99%